Macroalgae of the lagoon of “El Carmen”, Tabasco, Mexico - Pérez Jiménez, Graciela María; Rivas-Acuña, Ma. Guadalupe; León Álvarez, Daniel; Campos Campos, Bernardita; Quiroz-González, Nataly (Instituto de Ecología, A.C., 2020)
Background and Aims: Due to the lack of knowledge about macroalgae in Tabasco’s coastal lagoons, this work was determined in three seasons, the macroalgae diversity associated to the El Carmen lagoon, municipality of Cardenas and contributes to the biological and ecological knowledge of the state of Tabasco, Mexico. Methods: Three samplings were carried out in an annual cycle from 2015 to 2016, during the rainy, northern wind and dry seasons. The organisms were collected manually, fixated with seawater and 4% formalin, identified, and deposited in the UJAT and FCME (UNAM) herbaria. Key results: Twenty-one species of marine macroalgae were recorded, of which three are new records for the state of Tabasco. The Rhodophyta division with the families Gracilariaceae and Rhodomelaceae had the highest species richness and Gracilaria blodgetti was the most abundant species. The greatest diversity and abundance appeared in the northern wind season. Conclusions: There is an increase to 125 species in the number of records of Rhodophyta species and 28 in the Ochrophyta for Tabasco. Hence, it is suggested to extend the sampling time and perform systematic work in an annual cycle, in order to have a better representation of the diversity and seasonality of the macroalgae in the El Carmen lagoon.